2006
DOI: 10.1007/s00253-006-0458-7
|View full text |Cite
|
Sign up to set email alerts
|

Production of polyhydroxyalkanoates from methanol by a new methylotrophic bacterium Methylobacterium sp. GW2

Abstract: A new bacterial strain, isolated from groundwater contaminated with explosives, was characterized as a pink-pigmented facultative methylotroph, affiliated to the genus Methylobacterium. The bacterial isolate designated as strain GW2 was found capable of producing the homopolymer poly-3-hydroxybutyrate (PHB) from various carbon sources such as methanol, ethanol, and succinate. Methanol acted as the best substrate for the production of PHB reaching 40 % w/w dry biomass. PHB accumulation was observed to be a grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 22 publications
1
34
0
8
Order By: Relevance
“…This indicated that methanol is the principal precursor for PHA synthesis by strain Azu-IN1 as previously reported [33][34]. Besides, the recovery yield is superior to that obtained to Yezza et al, [35] who reported that, after 66 h, a copolymer content of 30 % (w/w) was achieved when 1 % (v/v) methanol solution supplemented with 0.1 % (v/v) valeric acid used as substrate. In addition, the yield (Y p/s ) of 0.228 g/g obtained in this study is about 84.5 % of the maximum theoretical yield based on glycerol (0.47 g/g) via acetyl-CoA pathway [22].…”
Section: Discussionsupporting
confidence: 54%
“…This indicated that methanol is the principal precursor for PHA synthesis by strain Azu-IN1 as previously reported [33][34]. Besides, the recovery yield is superior to that obtained to Yezza et al, [35] who reported that, after 66 h, a copolymer content of 30 % (w/w) was achieved when 1 % (v/v) methanol solution supplemented with 0.1 % (v/v) valeric acid used as substrate. In addition, the yield (Y p/s ) of 0.228 g/g obtained in this study is about 84.5 % of the maximum theoretical yield based on glycerol (0.47 g/g) via acetyl-CoA pathway [22].…”
Section: Discussionsupporting
confidence: 54%
“…Whereas Yamane et al (1996) produced PHB with a M n of 172×10 3 (M w /M n 1.84) in a high-cell-density fedbatch culture of A. latus using a sucrose-based medium. Discrepancy between M n obtained in our study and those of Yamane et al (1996) could be attributed to the differences in growth conditions, biopolymer extraction, purification techniques, or the purity of samples (Rehm 2003;Yezza et al 2006). The molecular weight of polymers is believed to be one of the most important factors affecting their physicochemical and mechanical properties and thus their applications.…”
Section: Discussionmentioning
confidence: 93%
“…The HV source might be poly 3-hydroxybutyrate-co-3-hydroxyvalerate (PHBV) known to be available in soil film and degraded by microbial activity especially by some fungal strains (Sang et al 2002). The production of PHBV in soil is associated with some bacterial strains such as Methylobacterium organophilum under nitrogen limitation (Yezza et al 2006). In our study, the increase of hydroxyvalerate was reflected on foxtail shoots uptake in the groups treated with mycorrhiza only (EC and EN) and showed a positive correlation with foxtail height and fresh and dry biomass.…”
Section: Discussionmentioning
confidence: 99%